Increasing incidence and mortality related to liver cancer in Australia: time to turn the tide. (8th April 2019) - Cocker, Fiona; Chien Yee, Kwang; Palmer, Andrew J.; de Graaff, Barbara
Abstract: Objective : Assess national and jurisdictional incidence and mortality trends for primary liver cancer in Australia. Methods : Analysis of Australian Cancer Incidence and Mortality data published in 2017 by the AIHW. Age‐standardised rates (ASR) for 1982 to 2014/2015. Piecewise linear regression was used to assess temporal trends. For the purposes of comparison, data were also extracted for all cancers with greater burdens of disease (lung, colorectal, breast, prostate, pancreatic, and brain cancers and melanoma of the skin). Results : Since 1982, the average annual percentage change (AAPC) for ASR incidence of liver cancer was 4.858% (95%CI 4.558–5.563). This marked a 306% increase from 1.822/100, 000 persons (95%CI 1.586–2.058) in 1982 to 7.396/100, 000 persons (95%CI 7.069–7.723) in 2014. AAPC for ASR mortality was 3.013% (95%CI 2.448–3.521): an increase of 184% from 2.323/100, 000 persons (95%CI 2.052–2.594) in 1982 to 6.593/100, 000 (95%CI 6.290–6.896) in 2015. ASR incidence and mortality were highest in the NT (12.607/100, 000 persons), VIC (8.229/100, 000) and NSW (7.798/100, 000). In comparison to the other selected cancers, higher AAPC for both incidence and mortality of liver cancer were observed. Conclusion : Incidence and mortality associated with liver cancer have increased substantially in the past three decades, in contrast to the improved outcomes observed for many other cancers. Jurisdictional incidence rates reflect higher prevalence of hepatitis B and C. Implications for public health : In the context of Australian cancer prevention and care programs, liver cancer is an outlier. Strategies to mitigate risk factors and improve surveillance of liver health for at‐risk groups are urgently required.